Introduction: The North Atlantic Triangle: ‘For and Against?’ - Silver, Lara C. A. (London journal of Canadian studies, 2025)
This introduction provides some necessary background to the origins of John Bartlet Brebner’s North Atlantic Triangle: The Interplay of Canada, the United States, and Great Britain, published in 1945, which is the subject of this special issue of the London Journal of Canadian Studies. The author – and guest editor of this issue of the journal – also reflects upon the differing views of the journal’s eminent contributors on the significance of the ‘North Atlantic Triangle’ concept that has been regularly debated by historians and political scientists – Canadian, British and American – ever since the book was first published.